Pregnancy Is a Survival Pathology: A Biostatistical Approach - Zhou, Jolie (Philosophy of Medicine, 2025)
This paper argues that biostatistical theory (BST) cannot categorically exclude pregnancy from pathology. Common harmful conditions in typical pregnancies are integral to the notion of pregnancy per se. Given this definition, there are two potential ways to classify pregnancy as non-pathological within the BST: (i) most common conditions in pregnancy are not pathological within the appropriate reference class; or (ii) pregnancy’s reproductive value counterbalances its pathological survival harms, rendering it non-pathological. I challenge both views, arguing that non-pregnant women of the same age should be the reference class, making pregnancy a survival pathology that cannot be offset by reproductive value.